2001
DOI: 10.2330/joralbiosci1965.43.676
|View full text |Cite
|
Sign up to set email alerts
|

Histological Changes in the Rat Submandibular Gland Following Ligation and Removal of the Main Excretory Duct. New Findings on Acinar Atrophy and Regeneration.

Abstract: Abstract:The present study was conducted to clarify the histological changes in the a cinar and myoepithelial cells of the rat submandibular gland after ligation of the main excretory duct for one week, and also the regenerative movements of these cells after ligation release . Tissue specimens were subjected to immunostaining and TUNEL staining , and examined by light microscopy. Some of the samples were prepared for transmission electron microscopy by a routine method . Duct-like structures covered with myoe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 12 publications
1
10
0
Order By: Relevance
“…Consequently on the 6th to 7th day after ligation, no acinar cells survive and only duct-like structures are present sparsely in the glands. When the ligation is release, acinar cells are progressively regenerated (Standish and Shafer 1957;Hanks and Chaudhry 1971;Yagishita et al 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently on the 6th to 7th day after ligation, no acinar cells survive and only duct-like structures are present sparsely in the glands. When the ligation is release, acinar cells are progressively regenerated (Standish and Shafer 1957;Hanks and Chaudhry 1971;Yagishita et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is important to elucidate how the function and morphology of the salivary glands recover from the duct obstruction disorders. It is known that the artifi cial closure of the submandibular main excretory duct of rodents results in disappearance of the acinar architecture, and that the release of the duct ligation leads to the regeneration of acini (Standish and Shafer 1957;Hanks and Chaudhry 1971;Yagishita et al 2001). Hitherto, the molecular mechanisms of the acinar regeneration as well as the identifi cation of histochemistry and hematoxylin-eosin (H-E) staining.…”
Section: Fixation and Stainingmentioning
confidence: 99%
“…Histologically, atrophy and disappearance of acinar cells, and gradual increases in duct-like structures and fibrous connective tissue were observed. Changes in salivary gland tissue after short-term ligation that have been reported include enlargement of duct lumens, atrophy and disappearance of acinar cells above the ligation, increases in ductlike structures and proliferation of fibrous connective tissue, degranulation and vacuolar degeneration of granular duct cells and acinar cells, and disappearance of basal striations from the striated duct [8][9][10][11][12][13][14][15][16][17][18] . This was similar to findings in the long-term ligation.…”
Section: Discussionmentioning
confidence: 99%
“…Histological studies of atrophied salivary glands have reported the occurrence of duct-like structures 17,18,[29][30][31] . Duct-like structures resulting from ligation were also observed in the present study, and it was shown that these increase over time with long-term ligation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation